Project “Transformation Processes in Oasis Settlements in Oman” Report on the survey campaign spring 2003 in Maqta‘ and Ibrā’ - Häser, Jutta (2003)
Keywords: Archéologie -- Oman

Project “Transformation Processes in Oasis Settlements in Oman” Report on the survey campaign autumn 2003 in Ibrā’ and al-Hamrā’ - Häser, Jutta; Schreiber, Jürgen (2003)
Keywords: Archéologie -- Oman

Le style épistolaire comme source de l’œuvre religieuse à Tunis et à Djerba - Cohen, Biniyamin Raphael (Les Juifs de Tunisie : création, tradition et culture, 2003)
Keywords: Judaïsme -- Djerba

Arabisation, francisation et tradition juive à Djerba - Deshen, Shlomo (Les Juifs de Tunisie : création, tradition et culture, 2003)
Keywords: Judaïsme -- Djerba

Les poèmes liturgiques des femmes de Djerba - Guez-Avigal, Miriam (Les Juifs de Tunisie : création, tradition et culture, 2003)
Keywords: Judaïsme -- Djerba

Les sources de quelques traditions de Djerba - Ripeld, Meyer (Les Juifs de Tunisie : création, tradition et culture, 2003)
Keywords: Judaïsme -- Djerba

L’ile de Djerba : Le lieu et la Légende: examen de récits populaires - Sarig, Yaakov (Les Juifs de Tunisie : création, tradition et culture, 2003)
Keywords: Judaïsme -- Djerba

Kissé Rahamim » sur le Talmud du rabbin Rahamim Houri de Djerba - Arned, Aharon (Les Juifs de Tunisie : création, tradition et culture, 2003)
Keywords: Judaïsme -- Djerba

al-Buʿd al-Tārīkhī li-Shurūḥāt al-Manẓūmāt al-ʿAqadiyya: al-Daʿā’im li-Ibn al-Naḍr al-Ibāḍī Unmūdhajan - Salimi, Abdulrahman al- (2003)

Tārīkh Ṣuḥuf Abī ‘l-Yaqẓān: Qirā’a Taḥlīliyya - Nāṣir, Muḥammad Ṣāliḥ (Mahrajān al-Ṣiḥāfī al-Shaykh Abī ‘l-Yaqẓān Ibr. fī ‘l-Dhikrà al-thalāthīn li-Wafātihi, 1973-2003, 2003)
Keywords: Journalisme -- Mzab

Tārīkh al-Jazā’ir min khilāl Ṣuḥuf al-Shaykh Abī ‘l-Yaqẓān - Ibn ʿUmar, al-Ḥājj Mūsà b. Bakīr (Mahrajān al-Ṣiḥāfī al-Shaykh Abī ‘l-Yaqẓān Ibr. fī ‘l-Dhikrà al-thalāthīn li-Wafātihi, 1973-2003, 2003)
Keywords: Abū ‘l-Yaqẓān, Ibrāhim (1888-1973); Journalisme -- Mzab

Ahammiyyat Qirā’at Fikr al-Shaykh Abī ‘l-Yaqẓān - Būḥajjām, Muḥammad b. Qāsim Nāṣir (Mahrajān al-Ṣiḥāfī al-Shaykh Abī ‘l-Yaqẓān Ibr. fī ‘l-Dhikrà al-thalāthīn li-Wafātihi, 1973-2003, 2003)

Ṣiḥāfat Abī ‘l-Yaqẓān fī ʿAyn al-Shaykh ʿAbd al-Raḥmān [b. ʿUmar Bakillī] - Bājū, Muṣṭafà b. Ṣāliḥ (Mahrajān al-Ṣiḥāfī al-Shaykh Abī ‘l-Yaqẓān Ibr. fī ‘l-Dhikrà al-thalāthīn li-Wafātihi, 1973-2003, 2003)
Keywords: Abū ‘l-Yaqẓān, Ibrāhim (1888-1973); Journalisme -- Mzab

al-Shaykh Abū ‘l-Yaqẓān wa’l-Maṭbaʿa al-ʿArabiyya - Bāḥarīz, Ibrāhīm (Mahrajān al-Ṣiḥāfī al-Shaykh Abī ‘l-Yaqẓān Ibr. fī ‘l-Dhikrà al-thalāthīn li-Wafātihi, 1973-2003, 2003)
Keywords: Abū ‘l-Yaqẓān, Ibrāhim (1888-1973); Journalisme -- Mzab

News from the West. Letters from Oman, 1798-1806 - Witkam, Jan Just (2003)
Published at the occasion of the visit to Leiden University Library by H.E. the Minister of Awqaf and Religious Affairs of the Sultanate of Oman, Shaikh Abdullah bin Mohammed bin Abdullah al Salimi on Friday 11 July 2003. Presentation of manuscripts Or. 2241-IV (11, 2-10) in the University Library Leiden. Letters of Sultans Sulṭān b. Aḥmad b. Saʿīd and Badr b. Sayf b. Aḥmad b. Saʿīd al-Būsaʿīdī to the Dutch Governor-General in Batavia (in present-day Indonesia).
Keywords: Relations -- Oman -- Pays-Bas

Wājib al-ʿInāya bi’l-Turāth: al-Shaykh Abū ‘l-Yaqẓān Namūdhajan - Wumūsà, Muḥammad ʿĪsà (Mahrajān al-Ṣiḥāfī al-Shaykh Abī ‘l-Yaqẓān Ibr. fī ‘l-Dhikrà al-thalāthīn li-Wafātihi, 1973-2003, 2003)
Keywords: Abū ‘l-Yaqẓān, Ibrāhim (1888-1973)

Maḥaṭṭāt Fikriyya fī Ṣiḥāfat Abī ‘l-Yaqẓān - Zaghīna, Muḥammad (Mahrajān al-Ṣiḥāfī al-Shaykh Abī ‘l-Yaqẓān Ibr. fī ‘l-Dhikrà al-thalāthīn li-Wafātihi, 1973-2003, 2003)
Keywords: Abū ‘l-Yaqẓān, Ibrāhim (1888-1973); Journalisme -- Mzab

Leadership and scholarship in Oman's modern Ibadi renaissance - Hoffman, Valerie J. (Middle East Studies Association of North America, 2003)
Paper presented at the Middle East Studies Association of North America (MESA) annual meeting, Anchorage, Alaska, 9 Nov. 2003.